Quel traitement lexicographique de l’onomastique commerciale ? Pour une distinction Nom de marque/Nom de produit - Christine Fèvre-Pernet; Michel Roché (Corela, 2005)
The lexicographical account of trade names, trademarks or “brand names” poses several problems. In this paper, we propose to show, by taking into account several criteria, that brand names and product names constitute two distinct classes in commercial onomastics. They behave differently in many respects : pragmatically (origin or content identification, the need for providing a name), referentially (nature of referent, distinctive function), syntactically (information packaging and utterance syntax). Brand names and product names can be distinguished on a morphological basis, taking into account their mode of construction. The lexical point of view will be developed in four directions : the extent to which these items belong to the speaker’s lexical competence, their integration into the lexicon in response to a naming need, cohyponymic and hyperonymic links with other items of the lexicon, and the lexicographical recording of these names. The semantic criterion is particularly useful for giving brand and product names the status of proper names or of common nouns.